Pengaruh Kepemimpinan Transformasional, Pengawasan Dan Etika Kerja Terhadap Disiplin Kerja Pegawai Pada Biro Umum Sekretariat Daerah Aceh - Nilawati Nilawati (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study was to determine and analyze the effect of transformational leadership, supervision and work practices on the work discipline of public bureau employees and the Aceh regional secretariat either partially or simultaneously. The approach used in this study is an associative approach. The population in this study were all employees of the public bureau and the Aceh regional secretariat totaling 230. The sample in this study used the Slovin formula, totaling 70 employees of the general bureau and the Aceh regional secretariat. Data collection techniques in this study using interview techniques, documentation study, observation, and questionnaires. Multiple Liner Regression Analysis Test, Hypothesis Test (t test and F test), and coefficient of determination were used in the data analysis methodology in this study. The software program SPSS (Statistical Kit for Social Sciences) version 24.00 was used for data analysis in this report. The results of this study prove that partially and simultaneously transformational leadership, supervision and work activities have a significant effect on the work discipline of employees of the general bureau and the Aceh regional secretariat.